2018
DOI: 10.5603/kp.a2017.0263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prevalence of periodontal disease as a non-classical risk factor in the group of patients undergoing hip and/or knee arthroplasty

Abstract: In conclusion, periodontal diseases are highly prevalent in patients undergoing hip and/or knee replacement surgery. The presence of the periodontal disease is possibly associated with a worse prognosis and should be treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 9 publications
5
21
0
Order By: Relevance
“…Only a few studies have examined dental pathology in patients planning to have a hip or knee arthroplasty. These studies have found that 23% of patients required treatment for dental infection or caries (8), 12% had an infection requiring root canal treatment or tooth extraction (9), and 29% had clinically significant periodontal disease (10). Periodontal health has been shown to affect the incidence of daily oral bacteremia, and infection incorporating the entire periodontium is equivalent to a wound area of 20 cm 2 (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined dental pathology in patients planning to have a hip or knee arthroplasty. These studies have found that 23% of patients required treatment for dental infection or caries (8), 12% had an infection requiring root canal treatment or tooth extraction (9), and 29% had clinically significant periodontal disease (10). Periodontal health has been shown to affect the incidence of daily oral bacteremia, and infection incorporating the entire periodontium is equivalent to a wound area of 20 cm 2 (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies were included[12-19]. Of the 8, 7 (86%) included a dental evaluation performed by a dental professional[12-14,16-19] and five utilized questionnaires or interviews (71%)[13-17]. One paper used a questionnaire alone[15].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies focused on the prevalence of dental pathology and/or dental hygiene practices in patients to undergo TJA (Table 3)[12-15]. Adamkiewicz et al[12] had dental evaluations performed on patients admitted for TJA preoperative workup in Poland. They found that 28.5% had clinically significant periodontal disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal disease has also been identified as a non-classical risk factor that is highly prevalent in general population and especially significant in patients undergoing knee and hip replacement surgery [8]. It is hypothesised to contribute to cardiovascular risk through bacteria activating host inflammatory responses that can lead to systemic inflammation [9].…”
Section: Introductionmentioning
confidence: 99%